2003
DOI: 10.1128/jcm.41.9.4154-4159.2003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Immune-Complex-Dissociated Nonstructural-1 Antigen in Patients with Acute Dengue Virus Infections

Abstract: Accurate and timely diagnosis of dengue virus (DEN) infections is essential for the differential diagnosis of patients with febrile illness and hemorrhagic fever. In the present study, the diagnostic value of a newly developed immune-complex dissociated nonstructural-1 (NS-1) antigen dot blot immunoassay (DBI) was compared to a commercially available DEN antigen detection kit (denKEY Blue kit; Globio Co., Beverly, Mass.) and a reverse transcription-PCR (RT-PCR) kit. Serial serum or plasma samples (n ‫؍‬ 181) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
1
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 18 publications
7
94
1
6
Order By: Relevance
“…Our observation of a reduced sensitivity of NS1 assays for secondary dengue infections is in agreement with previous findings (Koraka et al 2003, Kumarsamy et al 2007, Blacksell et al 2008. The possibility of anti-NS1 antibodies resulting from a previous infection in quenching the NS1 antigen of a current infection has been discussed to explain this observation (Valdes et al 2000, Libraty et al 2002, Koraka et al 2003.…”
Section: Ns1 Antigen Assays For Dengue Diagnostics and Surveillancesupporting
confidence: 82%
See 2 more Smart Citations
“…Our observation of a reduced sensitivity of NS1 assays for secondary dengue infections is in agreement with previous findings (Koraka et al 2003, Kumarsamy et al 2007, Blacksell et al 2008. The possibility of anti-NS1 antibodies resulting from a previous infection in quenching the NS1 antigen of a current infection has been discussed to explain this observation (Valdes et al 2000, Libraty et al 2002, Koraka et al 2003.…”
Section: Ns1 Antigen Assays For Dengue Diagnostics and Surveillancesupporting
confidence: 82%
“…The possibility of anti-NS1 antibodies resulting from a previous infection in quenching the NS1 antigen of a current infection has been discussed to explain this observation (Valdes et al 2000, Libraty et al 2002, Koraka et al 2003. Nevertheless, NS1 assay was found to have around 50% sensitivity among secondary dengue infections in Singapore, where approximately 45% of dengue cases are secondary infections (Low et al 2006).…”
Section: Ns1 Antigen Assays For Dengue Diagnostics and Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…12 A study conducted by Koraka et al in 2003 showed that antigen detection was low in endemic area due to formation of immune complexes following a secondary dengue infection and inappropriate temperature storage of samples. 13 So it is important that samples are collected, stored and transported properly to maintain the quality and stability of samples tested.…”
Section: Combination Of Dengue Ns1 Antigen and Antibody Testsmentioning
confidence: 99%
“…Dengue NS1 antigen and Dengue specific IgA antibody based assays have been shown to be useful during early febrile days. [5][6][7][8][9][10][11][12][13][14][15][16][17] ELISA and ICT based NS1 assay have been used as a diagnostic tool during febrile phase till defervescence (1 -9 days of fever onset) however, due to presence of virus -IgG immunocomplexs this assay has shown to be less sensitive in secondary infection as compared to primary infections 18,19 and may give false negative results in dengue endemic and hyperendemic areas. Studies comparing sensitives and specificities of IgA and NS1 reported dengue IgA to be more sensitive during early febrile phase of both primary and secondary dengue infection.…”
Section: -416mentioning
confidence: 99%